San Pedro el Alto, Oaxaca, Mexico: example of community forest management that triggers socioeconomic progress - Serrano-Ramírez, Elizabeth (2022)
Community forest management in México is a management scheme that strengthens the local development, mainly in low-income communities. It allows them to reduce their marginalization conditions and preserve the ecosystem’s biodiversity and the population's cultural wealth. To know the impact of this type of management in those communities that have used it, this paper presents the socioeconomic characterization of San Pedro el Alto, a community that has successfully executed community forest management for around 35 years. The information was collected through a survey that considers variables referring to income, education, employment, health, and housing. The results indicate that the forest management used by the community is positively reflected in the standard of living of its inhabitants, also preserving their cultural features. However, significant areas for improvement were also identified, such as the educational lag in its youth population.